An assessment tool of sustainable design and construction activities for green highway - Raja Muhammad Rooshdi, Raja Rafidah (2020)
The construction industry is one of the major contributors to the CO2 emission which cause environmental impacts on the earth‘s climate. Malaysian government is committed in reducing the CO2 by 40% in 2020 and 45% by 2030 as compared to the levels in 2005. Hence, there is a need to reduce the impact on the environment. Currently, there is no specific tool or standard of green highway assessment for the tropical region. Therefore, the main objective of this study is to develop an assessment tool for sustainable design and construction activities for highway development. Basically, the approach used in this study is to identify the significant criteria for sustainable design and construction activities and to determine the weightage and score for each criterion. The development of an assessment tool was based on the score for each criterion and the validation of an assessment tool was carried out by using the case studies. The significant criteria on established sustainable design and construction activities for green highway consist of construction management plan, noise mitigation control, equipment and machinery efficiency, quality management, context-sensitive design, erosion and sedimentation control, alignment selection, reused and recycled non-hazardous materials, recycled materials for subgrade improvement/soil stabilization and usage of local materials generated through survey and expert discussion. Questionnaires were developed and distributed to 140 respondents consisting of highways experts from concessionaires company, consultants, and engineers to obtain the agreement levels of listed criteria of sustainable design and construction activities for green highways. The weightage and score point were obtained on analyzed data using factor analysis from the Statistical Package for Social Science (SPSS) version 20 software. The weightage of each criterion was used to rank the criteria based on the importance of the criteria at the design and construction activities stages. The results showed that there are seven main criteria of design and construction activities for green highway development. Construction management plan is the most important criteria for achieving green highway development in Malaysia and followed by noise mitigation, equipment and machinery, quality management, context sensitive design, erosion and sedimentation control and alignment selection. All the main criteria and sub criteria had been developed into an assessment tool as a scorecard. In conclusion, the development of scorecard as an assessment tool of sustainable design and construction activities had been validated and is essential for green highway in Malaysia.